2023
DOI: 10.1038/s41467-022-35722-3
|View full text |Cite
|
Sign up to set email alerts
|

The effect of DNA polymorphisms and natural variation on crossover hotspot activity in Arabidopsis hybrids

Abstract: In hybrid organisms, genetically divergent homologous chromosomes pair and recombine during meiosis; however, the effect of specific types of polymorphisms on crossover is poorly understood. Here, to analyze this in Arabidopsis, we develop the seed-typing method that enables the massively parallel fine-mapping of crossovers by sequencing. We show that structural variants, observed in one of the generated intervals, do not change crossover frequency unless they are located directly within crossover hotspots. Bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 93 publications
2
13
1
Order By: Relevance
“…A recent study showed that the megabase-scale CO landscape in A. thaliana is mostly explained by association with (epi)genetic marks beyond a centromere effect, with open chromatin states showing the highest positive correlation with CO formation 15 . While single nucleotide polymorphisms only showed a rather local effect on CO positioning 15,62 . In contrast to these organisms, we could only find correlation of CO positioning with centromere and (epi)genetic features at a very fine-scale.…”
Section: Discussionmentioning
confidence: 95%
“…A recent study showed that the megabase-scale CO landscape in A. thaliana is mostly explained by association with (epi)genetic marks beyond a centromere effect, with open chromatin states showing the highest positive correlation with CO formation 15 . While single nucleotide polymorphisms only showed a rather local effect on CO positioning 15,62 . In contrast to these organisms, we could only find correlation of CO positioning with centromere and (epi)genetic features at a very fine-scale.…”
Section: Discussionmentioning
confidence: 95%
“…Crossover tactics include discrete recombination, intermediary recombination, and linear recombination, which are actual crossovers, and binary crossovers . In this study, we offer a novel crossover technique for bringing on new hires [19]. In genetic algorithms, the crossover is typically performed by selecting a crossover point along the chromosome and swapping genetic material between two parent individuals to create one or more offspring individuals.…”
Section: Crossovermentioning
confidence: 99%
“…In eukaryotes, heterodimers of bacterial MutS homologues (MSHs) that bind mismatched bases are responsible for detecting interhomolog polymorphism 54,58,59 . All MSH dimers involved in mismatch detection are assumed to contain the MSH2 protein 49,50,54,[58][59][60] . Therefore, we investigated whether inactivation of MSH2 would increase the fertility of fancm zip4 Col/Ler hybrids.…”
Section: Msh2 Limits Fertility Of Fancm Zip4 Hybridsmentioning
confidence: 99%
“…The msh2-1 T-DNA insertion line (SALK_002708) and Arabidopsis accessions Col, Ler and Ct were obtained from the Nottingham Arabidopsis Stock Centre (NASC). The msh2-2, msh2-3, msh2-4, msh2-5 (in Col/Ct recombinant lines) and msh2-6 (in Ler−0) deletion mutants were previously generated in our laboratory via CRISPR/ Cas9 mutagenesis 49,50 , as well as Ler zip4-3 mutant generated in this study. The HEI10-OE line corresponds to transgenic line "C2", previously described in ref.…”
Section: Growth Conditions and Plant Materialsmentioning
confidence: 99%
See 1 more Smart Citation